The Influence of Work Discipline on Employee Performance Through Work Loyalty of Employees of the Ministry of Religion of Sidoarjo Regency - Izzul Afghani (Universitas Negeri Surabaya, 2025)
This research was conducted at the Ministry of Religious Affairs of Sidoarjo Regency to examine the relationship between employee performance, loyalty, and work discipline. This study uses a quantitative method. The sampling technique employed non-probability sampling with a saturated sample, where the entire population, totaling 81 respondents, was used as the sample. The statistical analysis used in this study is the Structural Equation Model – Partial Least Square (SEM-PLS) with SmartPLS 3.0 software. The results of the study indicate that loyalty positively affects work discipline, where more disciplined employees tend to exhibit stronger loyalty and emotional attachment to the organization. Loyalty acts as a mediator that strengthens the impact of work discipline on performance. Additionally, work discipline directly influences performance improvement by creating an orderly and productive work environment. This study asserts that enhancing work discipline that fosters loyalty can significantly improve employee performance.